Ectopic Papillary Carcinoma in the Midline Neck Accompanied by a Benign Thyroid Gland. (10th January 2019) - Evans, Lauran; Park, SeHoon; Elliott, Christie; Garrett, Courtney
Abstract : Ectopic thyroid tissue can deposit anywhere in the body. There are several cases reporting papillary thyroid carcinoma (PTC) arising from ectopic tissues; however, these cases largely presented with primary PTC within the native thyroid gland as well. Alternatively, some cases report of PTC found solely in an ectopic thyroglossal duct cyst, but reports of isolated malignancy in other types of ectopic thyroid tissue with normal native tissue are sparse throughout the literature. Here, we present an unusual case of PTC in the midline anterior neck that does not appear to be consistent with a thyroglossal duct cyst, accompanied by a completely benign native thyroid gland, of which only few cases have been reported.